Stakeholder perception of the ethics of an industry: The case of organic food in South India - Jacob-John, Jubin; Veerapa, Navin (European Journal of Sustainable Development, 2015)
Abstract Increasing reliance on artificial and non-sustainable methods of agriculture had resulted in negatively affecting both the soil and the health of agriculturists. Organic agriculture abhors such conventional agricultural practices and inculcates the implementation of safer, socially responsible and environmentally sustainable agricultural practices. This paper analyses the stakeholders’ perception of responsibility and environmental sustainability by conducting qualitative research using case studies of several organic food supply chains based in Kerala, a state in the south of India. The interviews with key stakeholders along the supply chain network illustrate that the rationale for organic agriculture is based on principles of fairness, responsibility and sustainability. Furthermore, the results depict that perceptions of ethics vary amongst stakeholder groups. Thoughthe literature is extensive on business ethics and sustainability, research on stakeholder perception along the entire industry is minimal within academic literature and the paper contributes to this area. Furthermore, from a managerial perspective, this paper sheds light on the influence of business ethics within an industry and exhibits the importance and influence of social responsibility and environmental sustainability within an industry. Keywords: Ethics, food, sustainability, responsibility, agriculture, organic